Trends and Associations with PrEP Prescription Among 602 New York City (NYC) Ambulatory Care Practices, 2014–2016. (4th October 2017) - Salcuni, Paul; Smolen, Jenny; Jain, Sachin; Myers, Julie; Edelstein, Zoe
Abstract: Background: Concern over equitable access to HIV preexposure prophylaxis (PrEP) informs comprehensive scale-up efforts in New York City (NYC). We examined trends plus patient and practice factors associated with PrEP prescribing by NYC ambulatory care practices. Methods: We queried electronic health records (EHR) from Q1 2014 to Q2 2016 using the NYC Health Department's "Hub." Data from 602 practices were aggregated quarterly by patient factors, including age (18–29, 30–100); sex (male, female); and race/ethnicity (Asian, Black, Hispanic, White, other, missing). Practice factors included location (Manhattan, other); type (community health center [CHC], hospital, independent); number of infectious disease (ID) specialists; and proportion of patients (ranked by quartile) from high poverty neighborhoods (ZIP codes in which ≥20% of residents live below the federal poverty level). PrEP prescription was defined as tenofovir/emtricitabine prescription without other antiretrovirals or diagnoses of HIV, HIV-related opportunistic infections or hepatitis B. Rates were calculated per 10 5 patients seen. We used generalized estimating equations clustered by practice to examine trends overall and by sex, as well as associations among males. Factors and time interactions that were significant ( P < 0.05) in bivariate analysis were assessed for inclusion in the final model. Results: Overall, PrEP prescription rose from 38.9 per 10 5 in Q1 2014 to 418.5 per 10 5 in Q2 2016, a 976% increase. Increases were significant for both sexes ( P < .0001; Figure 1). In multivariate analysis (Table 1), PrEP prescription was associated with both patient (younger age, white race/ethnicity) and practice factors (Manhattan location, CHCs, and on-site ID specialists). While practices with a greater proportion of patients from high poverty neighborhoods were less likely to prescribe PrEP initially, this association weakened over time (Table 2). Conclusion: PrEP prescription increased over 9-fold from 2014 to 2016 among NYC ambulatory care practices, but disparities persisted. While efforts to promote PrEP may have helped attenuate the disparity by neighborhood poverty of the patient population, continued work may be needed to facilitate PrEP access for women, persons of color and for those in care at non-CHCs or practices outside of Manhattan. Disclosures: All authors: No reported disclosures.